Office Ergonomics Driven by Contextual Design. (July 2015) - Löffler, Diana; Wallmann-Sperlich, Birgit; Wan, Juri; Knött, Jennifer; Vogel, Anna; Hurtienne, Jörn
Following contextual design, we identified motivational and social aspects, as well as environmental factors of desk-based office workplaces, that contribute to sedentary behavior in the workplace. Through 10 full-day work observations, we gathered detailed qualitative data on why and when workers sit and unveiled tacit knowledge about habits and physical workplace layouts that favor prolonged sitting, complementing the mostly quantitative research done in the field. Developing social motivations for standing and walking, distributing frequently used objects to require more walking, and reducing the attractiveness of sitting turned out to be key drivers for reducing and interrupting sedentary behavior.